Loudness perceived by normal and abnormal ears as measured by stapedial reflex threshold - R, Rangasayee (Journal of All India Institute of Speech and Hearing)
Stapedial Reflex threshold has gained wide currency in the measurement of loudness experience. (Ewertsenef al, 1967; Flottorp, Djupesland and Wither, 1971 : Moller, 1961; Thomsen, 1955) of an acoustic stimulus